New Habitat Data of the Green-Winged Orchid (Anacamptis Morio L.) Located in the Surroundings of Eger, Hungary - Tamás Misik; Dóra Misik-Bartók (Journal of environmental geography, 2023)
In 2022, we identified two new habitats of the protected green-winged orchid (Anacamptis morio